2012
DOI: 10.5194/hess-16-685-2012
|View full text |Cite
|
Sign up to set email alerts
|

Soil weathering rates in 21 catchments of the Canadian Shield

Abstract: Abstract. Soil mineral weathering represents an essential source of nutrient base cation (Ca, Mg and K) for forest growth in addition to provide a buffering power against precipitation acidity for soils and surface waters. Weathering rates of base cations were obtained for 21 catchments located within the temperate and the boreal forest of the Canadian Shield with the geochemical model PROFILE. Weathering rates ranged from 0.58 to 4.46 kmol c ha −1 yr −1 and their spatial variation within the studied area was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The median base cation weathering rate was just 17 mmol c m −2 yr −1 and more than 80% (52 of 63) of the sites had a base cation weathering rate b40 mmol c m −2 yr −1 . These weathering estimates are at the lower end of weathering estimates for soils in other parts of Canada: base cation weathering rates for the soil rooting zone of 3-13 mmol c m −2 yr −1 (Nova Scotia: Whitfield et al, 2006); 58-446 mmol c m −2 yr −1 (Quebec: Houle et al, 2012); 21 -79 mmol c m −2 yr −1 (Ontario: Koseva et al, 2010); 0.1-8000 mmol c m −2 yr −1 (Saskatchewan: Whitfield and Watmough, 2012); and 19-351 mmol c m −2 yr −1 (British Columbia: Mongeon et al, 2010). Weathering rates in this study were estimated using PROFILE, which like all methods used to estimate base cation weathering rates, is associated with some uncertainties (Hodson and Langan, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The median base cation weathering rate was just 17 mmol c m −2 yr −1 and more than 80% (52 of 63) of the sites had a base cation weathering rate b40 mmol c m −2 yr −1 . These weathering estimates are at the lower end of weathering estimates for soils in other parts of Canada: base cation weathering rates for the soil rooting zone of 3-13 mmol c m −2 yr −1 (Nova Scotia: Whitfield et al, 2006); 58-446 mmol c m −2 yr −1 (Quebec: Houle et al, 2012); 21 -79 mmol c m −2 yr −1 (Ontario: Koseva et al, 2010); 0.1-8000 mmol c m −2 yr −1 (Saskatchewan: Whitfield and Watmough, 2012); and 19-351 mmol c m −2 yr −1 (British Columbia: Mongeon et al, 2010). Weathering rates in this study were estimated using PROFILE, which like all methods used to estimate base cation weathering rates, is associated with some uncertainties (Hodson and Langan, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…described in previous studies (Houle et al, 2012b;Augustin et al, 2015aAugustin et al, , 2016. In this region, the Canadian Shield is composed of bedrocks formed during the Precambrian, which consists mainly of igneous (granite, syenite, anorthosite) and metamorphic (gneiss, granitic gneiss, paragneiss) rocks.…”
Section: Study Sites and Samplingmentioning
confidence: 93%
“…The geochemical model PROFILE is widely used to evaluate chemical and geochemical processes involved in forest soils and watersheds (Koptsik et al, 1999;Duan et al, 2002;Duchesne and Houle, 2006;Sverdrup, 2009;Erlandson Lampa et al, 2020). Previous works have shown that PROFILE is enough powerful to reproduce spatial geographical gradients in WRs for relatively large areas with contrasted mineralogy (Houle et al, 2012b;Augustin et al, 2016), while yielding reliable BC WRs (Jönsson et al, 1995). Since soil temperature and moisture both greatly affect the chemical, physical, and biological processes that are occurring in soils, it is essential to better understand how climate change will affect resulting future soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Precambrian Shield in Canada is dominated by catchments with areas of hundreds or thousands of square kilometres and numerous smaller, but important, headwater catchments (Craig & Johnston, ; Creed, Beall, Clair, Dillon, & Hesslein, ; Houle et al, ). Glaciation from the last ice age has led to significant surface‐exposed bedrock outcrops and thin soil resting on top of Precambrian bedrock (Gunn, Steedman, & Ryder, ).…”
Section: Introductionmentioning
confidence: 99%